Colour symbolism and three colours of Sheihk Gâlib - Yildirim, Ali (My University, 2006)
Colours have been one of the most defining elements of men in their recognizing and describing objects and events. Including man, everything has its colour which distinguishes it from others. By the time it has been understood that colours aren't only in relation with their appearence but also with their inner world. And so it has been proved scientifically that each colour has its pyschological effects on men. This is the reason why colours have had many symbolic meanings by the time. In this study we dealt with the symbolic quality of colours especially in Sufism and in two gazels of Sheihk Gâlib's of which redif consists of "white", "black" and "red".
Renk si?mgeci?li??i? ve Şeyh Gâli?b'i?n üç rengi?
Keywords: Colours; Gazel; Sheihk Gâlib; Sufism; Symbol